A construção da liberdade: vivências da escravidão e do pós-abolição. Mariana, 1871-1920 - Marileide Lazara Cassoli Meyer (2015)
This aim of this study is to analyze the process of "construction of liberty" that guided the formation of the free labor market in Brazil throughout the nineteenth century and early twentieth century. We sought to understand the gap between the coeval projects made viable by the state aiming to control and fix the freed manpower - and the social dynamics that effectively shaped society in terms of labor relations, political rights and citizenship in the post-abolition era. With this in mind, we turned our attention to the Municipality of Mariana, Minas Gerais, between 1871 and 1920. From the analysis of a diverse body of documents such as parish records, civil records, post-mortem inventories, tax and production registries, criminal records and provincial and police reports, we investigated the family ties and social networks constructed by former slaves, as well as the impacts of these "experiences" of slavery on their life of freedom.